Pasambahan dalam Upacara Khatam Al Quran di Nagari Tabek Patah Kecamatan Salimpaung Kabupaten Tanah Datar - Pratama, Nia Nadela; Hamidin, Hamidin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2013)
This study aimed to describe the structure, procedures, and functions khatam Al-Quran ceremony Pasambahan in Nagari Tabek Patah Salimpaung Kabupaten Tanah Datar. Studies theories used include (1) Pasambahan, (2) Pasambahan as oral Sastra, (3) Delivery 0f oral literature, (4) Pasambahan structure, (5) Pasambahan function, and (6) Al Quran khatam ceremony. This study uses descriptive qualitative kind. Pasambahan structure generally consists of four parts, namely the opening Sambah, Sambah statement, content delivery, and closing Sambah. Structure Pasambahan the Quran khatam ceremony consists of several stages Pasambahan delivery, first Pasambahan betel, Pasambahan juadah, Pasambahan eating, drinking, and Pasambahan khatam. Pasambahan has six function is the function of 1) the function of religion 2) custom function 3) moral function 4) educational function 5) the function of language and, 6) social functioning.